Pendidikan Kristiani Transformatif dalam Konteks Indonesia - Apriani Magdalena Sibarani; Tabita Kartika Christiani; Jozef M. N. Hehanussa (Sekolah Tinggi Teologi SAPPI Ciranjang, 2025)
This paper explores the development of transformative Christian education within the context of the Methodist Education in Indonesia. John Wesley emphasized morally grounded education for individual and societal transformation. Paulo Freire highlighted the importance of conscientization through liberative education. Tabita Christiani developed peace education approaches relevant to Indonesia's religious diversity. This study analyzes the educational approaches of these three figures to formulate a transformative Christian education model at SMA Methodist 1 Medan. This research uses a qualitative method with a conceptual-comparative analysis approach to the thoughts of John Wesley, Paulo Freire and Tabita Christiani, as well as a case study at Medan Methodist 1 High School. The findings reveal that transformative education goes beyond knowledge transfer, focusing on character formation and Christian values relevant to current social challenges. This model is expected to empower individuals to actively contribute to societal transformation toward justice and peace.